1996
DOI: 10.1007/pl00014256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of l-dopa on visual evoked potentials and neuropsychological tests in adult phenylketonuria patients

Abstract: Eight adult, untreated patients with classical phenylketonuria received L-dopa and a decarboxylase inhibitor for 2 weeks. No effect of L-dopa therapy on choice reaction time tasks, sustained attention, frontal lobal function as well as latencies of visual evoked potentials was found. The results raise the question if adult patients with phenylketonuria really suffer from functional dopamine deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…However, there is a lack of correlation between these changes and the prolonged VEP latencies measured in adults and children (13). The second hypothesis implies deficient levels of dopamine in the eye and the brain (16). Dopaminergic transmission has been demonstrated in neurones in the retina (24) and the lateral geniculate nuclei (25), and dopamine levels are low in PKU (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a lack of correlation between these changes and the prolonged VEP latencies measured in adults and children (13). The second hypothesis implies deficient levels of dopamine in the eye and the brain (16). Dopaminergic transmission has been demonstrated in neurones in the retina (24) and the lateral geniculate nuclei (25), and dopamine levels are low in PKU (26).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the third positive peak (P3) is a late cognitive potential that has a larger amplitude if a stimulus is infrequent and task-relevant (for review, see (8)). ERPs have excellent temporal resolution; changes have been found in the early peaks of scalp-recorded potentials of children and adults with PKU (9)(10)(11)(12)(13)(14)(15)(16). PKU may also affect cognitive P3, as recent studies have shown that dopamine monotherapy in Parkinson's disease causes a reduction in P3 latency (17) for an auditory task.…”
mentioning
confidence: 99%
“…Following these lines of consideration, large doses of tyrosine or L-dopa were expected to have a positive effect. However, later studies with large doses of tyrosine or L-dopa did not show positive results (Lou 1994; Mazzocco et al 1992; Pietz et al 1995; Smith et al 1998; Ullrich et al 1996). …”
Section: Rationale B: Tyrosine And/or Tryptophan Supplementation To Imentioning
confidence: 98%
“…Of 15 studies reporting executive function assessments for adults with early-treated PKU and age/gender matched controls without PKU, 13 studies reported mean test scores with variance estimates and were subsequently included in the MA (Antenor-Dorsey et al, 2013;Burgard et al, 1997;Channon et al, 2007;Feldmann, Denecke, Grenzebach, & Weglage, 2005;Griffiths, Paterson, & Harvie, 1995;Luciana, Sullivan, & Nelson, 2001;Moyle, Fox, Bynevelt, Arthur, & Burnett, 2006Pietz et al, 1998Pietz et al, , 1995Ris et al, 1997;Sundermann et al, 2011;Ullrich et al, 1996). The MA effect sizes using Hedges g found significant differences between adults with early-treated PKU and unaffected controls of 0.74 for attention (11 study arms; 252 participants, p < 0.0001), 0.41 for inhibitory control (6 study arms; 119 participants, p = 0.047), and 0.43 for cognitive flexibility (7 study arms; 157 participants, p = 0.006).…”
Section: Meta-analysis: Executive Functionmentioning
confidence: 99%